2016
DOI: 10.1371/journal.pntd.0004732
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Phylogenetic Distributions and Population Dynamics of the Genus Histoplasma

Abstract: BackgroundHistoplasma capsulatum comprises a worldwide complex of saprobiotic fungi mainly found in nitrogen/phosphate (often bird guano) enriched soils. The microconidia of Histoplasma species may be inhaled by mammalian hosts, and is followed by a rapid conversion to yeast that can persist in host tissues causing histoplasmosis, a deep pulmonary/systemic mycosis. Histoplasma capsulatum sensu lato is a complex of at least eight clades geographically distributed as follows: Australia, Netherlands, Eurasia, Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
139
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(165 citation statements)
references
References 95 publications
12
139
4
1
Order By: Relevance
“…The evolutionary model was established as K2+G4. 17 phylogenetic groups were identified with similar distribution as reported by Kasuga, 2003 and Teixeira, 2016 (Figure 2).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The evolutionary model was established as K2+G4. 17 phylogenetic groups were identified with similar distribution as reported by Kasuga, 2003 and Teixeira, 2016 (Figure 2).…”
Section: Resultssupporting
confidence: 83%
“…Interestingly, these isolates have shown marked differences among them relative to other H. capsulatum groups. The works by Kasuga et al (1999, 2003), and Teixeira et al (2016) show a high degree of variability among the Colombian isolates by MLST. The Kasuga’s work placed the Colombian isolates in Latin American clades (LAm) LAm A, LAm B and 2 solitary lineages.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…These previous studies have typically revealed phylogeographic structure within species, with multiple cryptic lineages linked to geographic regions, leading to the conclusion that, for fungi, "nothing is generally everywhere" [54,55]. Subsequent studies have shown that lineages in some of these fungi (e.g., Fusarium graminearum and Histoplasma capsulatum) represent cryptic species [56,57]. An exception to this rule is Aspergillus fumigatus, which has very small (2-3 µm), wind-dispersed conidia.…”
Section: Discussionmentioning
confidence: 99%